Helicobacter pylori infection is not correlated with subclinical thrombocytopenia: A cross-sectional study. (May 2014) - Samson, Annette D.; Schipperus, Martin R.; Langers, Alexandra M. J.; Dekkers, Olaf M.
Abstract In a small percentage of patients with immune thrombocytopenia (ITP), H. pylori eradication has a positive effect on platelet counts. Whether H. pylori infection is associated with a lower thrombocyte count in persons without clinical ITP is unknown. We performed a cross-sectional study to compare thrombocyte count between H. pylori infected (n = 108) and H. pylori non-infected patients (n = 600) who underwent a diagnostic gastroscopy. The mean thrombocyte count in H. pylori negative patients was 257 × 109/l, in H. pylori positive patients 252 × 109/l (mean difference 5 × 109/l, 95% CI: −23 to 14). Subgroup analysis did not show significant differences either. In the patient group without apparent comorbidity, there were no subjects with thrombocyte counts <120. In 36 H. pylori positive patients in whom data post-eradication was available, platelet counts pre- and post-eradication were similar. In conclusion, this study could not demonstrate a lower thrombocyte count in H. pylori infected patients or in subgroups of H. pylori infected patients compared to non-infected subjects.